Factors impacting a patient’s selection of an otolaryngologist - Katelin R. Keenehan; Amanda G. Baanante; Arunima Vijay; Gaayathri Varavenkataraman; Michele M. Carr (PLoS ONE, 2025)
Objective How a patient chooses a physician has not been evaluated in otolaryngology. Our purpose was to determine which factors are important for people in the selection of an otolaryngologist. Methods This study is a cross-sectional survey study using Amazon Mturk. Demographic data was collected. Participants rated 24 factors related to choosing an otolaryngologist on a 10-point scale. Multiple choice questions queried preferences on a physician’s social media, clothing, gender, and personality. Results Out of 287 participants, 105 (36.6%) were female, 209 (72.8%) were between the ages of 25–40, and 252 (87.7%) identified as white. The majority of participants had primary residence in the southern US (N = 115, 38.3%) and were native-English speakers (N = 286, 99.7%). 254 (88.5%) had completed a Bachelor’s degree, 232 (80.8%) were employed in healthcare, 237 (82.6%) had prior experience being treated by an otolaryngologist, and 275 (95.8%) rated their health status as good or better. The most important factors for respondents in choosing an otolaryngologist were “surgeon’s explanation of their diagnosis and treatment”, “the quality of their surgeon’s office”, “favorable office location”, “the surgeon’s ability to grasp their problem”, “the surgeon’s professionalism”, and “the surgeon’s physical examination”. Regarding attire and personality, formal or business casual with a white coat was preferred (N = 124, 43.2%). Participants preferred surgeons with a combination of a professional and lighthearted personality (N = 145, 50.5%). Conclusion The way in which an otolaryngologist engages with and examines a patient is most important to the lay public, although reputation carries some importance in choosing a doctor.